Constructing "English+" teaching mode enabled by ChatGPT: Taking "English + IT" subject as an example. - Zhang, Ziyue (SHS Web of Conferences, 2024)
With the explosion of English subjects, graduates majoring in English are now facing the dilemma of losing social and employment competitiveness. The present study found that English can combine its designated education with other subjects to improve students' overall competence, and using the new artificial intelligence of ChatGPT may be a promising method to assist English language teaching. The research has conducted semi-structured interviews with five students studying "English Language and Data" subjects at a university in Zhejiang, China. Through the semi-structured interviews, all of the interviewees used ChatGPT during their studying life at university; they not only used ChatGPT in English major courses, but they also used it in IT-related courses more often, and they preferred using ChatGPT, believing it had more pros than cons. The results showed that ChatGPT had become a good tool for English language teaching and "English+" subject learning, and its future remains to be explored.